EFFECTIVENESS OF THE PLATELET-RICH PLASMA APPLICATION AT DIFFERENT SIMULATION PERIODS OF DEGENERATIVE DISC DISEASE IN RATS - Zaporozhan, V.M.; Appelhans, O.L.; Tsyurupa, O.V. (World of Medicine and Biology, 2020)
The article describes the study of the platelet-rich plasma application effectiveness for tissue regeneration of intervertebral discs in rats with simulated degenerative disk disease of the caudal vertebrae for 60 and 90 days. The experiment involved 80 rats, which were divided into four groups: Group I – rats with a simulated pathology without correction for 60 days, Group II – rats with a simulated pathology without correction for 90 days, Group III – rats with a pathology and its correction for 60 days, Group IV – rats with a pathology and its correction for 90 days. The described morphological changes in the invertebral disk tissue suggest that the application of platelet-rich plasma in the pathology simulation for 60 days leads to the degenerative process inhibition and restores the invertebral disk structure. The application of platelet-rich plasma for 90-day pathology simulation is less effective.
Keywords: degenerative disk disease; intervertebral disc; fibrous ring; nucleus pulposus; platelet-rich plasma